Estudos preliminares para o projeto de reforma de uma mini estação de tratamento de esgoto - Tersi Pereira, Marcela [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This study objective was to realize of preliminary studies to a mini treatment plant reform and reactivation project of the mini ecoefficient wastewater treatment plant - MiniEETERA, of State University of São Paulo (UNESP), campus of Guaratinguetá, to meet the constructive norms and laws applicable. The MiniEETERA was evaluated to verify the attendance of the implemented project to the initial purpose, as well as the conservation state of its components and the possible existence of pollution sources and unconformities, and to propose the reform and adequacy to the norms and laws, besides improvements. After these evaluations, a proposal of reform was elaborated to the adequacy and reactivation of the MiniEETERA, seeking the meeting with the norms, NBR 9648/1986, NBR 7229/1993, NBR 13.969/1997 and NBR 12209/2011. It was verified that some components of the plant did not correspond to the treatment proposed in the project. Sources of pollution and inadequacies to topics of all the norms considered were identified and advanced state of deterioration of the plant components was observed. It was also verified that the MiniEETERA worked for a small period of time (2007 to 2010), without applying the water reuse as it was determined in the Project. These preliminary studies were important to fundament the proposition of reform and adequacy of the MiniEETERA, being recommended the interdiction of this plant until the reform and adequacy of the MiniEETERA to the norms and Brazilian laws happens. This study was important because, after the adequacy, the MiniEETERA can be used in scientific studies. This work also contributes in the environmental and human safety protection

Este trabalho teve por objetivo realizar estudos preliminares para o projeto de reforma e reativação da mini estação ecoeficiente de tratamento de esgoto e reuso de água - MiniEETERA, da Universidade Estadual Paulista, campus de Guaratinguetá, visando o atendimento às normas construtivas e à legislação vigente. A MiniEETERA foi avaliada para verificar se o projeto implantado atendia em sua totalidade o tratamento proposto, bem como, o estado de conservação de seus componentes e a possível existência de fontes de poluição e inconformidades, visando a proposição de reforma e adequação às normas e legislação, além de melhorias. Após estas avaliações, foi elaborada uma proposta de reforma para a adequação e reativação da MiniEETERA, visando o atendimento às normas NBR 9648/1986, NBR 7229/1993, NBR 13969/1997 e NBR 12209/2011. Verificou-se que alguns componentes da estação não correspondem ao tratamento proposto no projeto. Foram identificadas fontes de poluição e inadequações à tópicos de todas as normas consideradas e observou-se estágio avançado de deterioração dos componentes da estação. Também foi constatado que a MiniEETERA funcionou por um curto período de tempo (2007 a 2010), sem aplicar o reuso de água, conforme projeto. Estes estudos preliminares foram importantes para fundamentar a proposta de reforma e adequação da MiniEETERA, sendo recomendada a interdição desta estação até a execução do projeto de reforma e adequação às normas e legislações brasileiras. Este trabalho foi importante, pois, após adequação, a MiniEETERA poderá ser utilizada em trabalhos científicos. Este trabalho também contribui na proteção ambiental e da saúde pública
Preliminary studies for the reform project of a mini sewage treatment plant
Keywords: Saneamento; Resíduos orgânicos; Esgotos; Água - Estações de tratamento; Organic wastes